Simple wet chemical synthesis of surfactant-free silver antimony sulphide (AgSbS2) flower-like nanostructures - E. Saksornchai (2018)
© 2017, National Institute R and D of Materials Physics. All rights reserved. Silver antimony sulphide (AgSbS2) flower-like nanostructures were successfully synthesized by a simple wet chemical method from silver nitrate (AgNO3), antimony chloride (SbCl3) and thioacetamide (C2H5NS) in ethylene glycol (EG) without using any surfactant. In this research, the first simple wet chemical method was developed for synthesizing AgSbS2nanostructures that very simple, rapid, surfactant-free, low-cost method and large-scale-production. X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) illustrate that the as-prepared products were cubic AgSbS2flower-like nanostructured clusters. The energy gap (Eg) was determined by UV-visible absorption to be 1.80 eV, including 688 nm emission wavelength by photoluminescence (PL) spectroscopy.